Chemically Induced Conditional Rescue of the Reduced Epidermal Fluorescence8 Mutant of Arabidopsis Reveals Rapid Restoration of Growth and Selective Turnover of Secondary Metabolite Pools. Issue 2 (31st December 2013) - Kim, Jeong Im; Ciesielski, Peter N.; Donohoe, Bryon S.; Chapple, Clint; Li, Xu
Abstract : Activation of the wild-type gene in an Arabidopsis phenylpropanoid mutant at different developmental stages has distinct impacts on metabolic changes and plant growth . Abstract: The phenylpropanoid pathway is responsible for the biosynthesis of diverse and important secondary metabolites including lignin and flavonoids. The reduced epidermal fluorescence8 ( ref8 ) mutant of Arabidopsis ( Arabidopsis thaliana ), which is defective in a lignin biosynthetic enzyme p -coumaroyl shikimate 3′-hydroxylase (C3′H), exhibits severe dwarfism and sterility. To better understand the impact of perturbation of phenylpropanoid metabolism on plant growth, we generated a chemically inducible C3′H expression construct and transformed it into the ref8 mutant. Application of dexamethasone to these plants greatly alleviates the dwarfism and sterility and substantially reverses the biochemical phenotypes of ref8 plants, including the reduction of lignin content and hyperaccumulation of flavonoids and p -coumarate esters. Induction of C3′H expression at different developmental stages has distinct impacts on plant growth. Although early induction effectively restored the elongation of primary inflorescence stem, application to 7-week-old plants enabled them to produce new rosette inflorescence stems. Examination of hypocotyls of these plants revealed normal vasculature in the newly formed secondary xylem, presumably restoring water transport in the mutant. The ref8 mutant accumulates higher levels of salicylic acid than the wild type, but depletion of this compound in ref8 did not relieve the mutant's growth defects, suggesting that the hyperaccumulation of salicylic acid is unlikely to be responsible for dwarfism in this mutant.